2018
DOI: 10.1128/mbio.01523-18
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Cholesteryl-α-Glucoside Transferase and Cholesteryl Glucosides in Maintenance of Helicobacter pylori Morphology, Cell Wall Integrity, and Resistance to Antibiotics

Abstract: Helicobacter pylori is an important cause of chronic gastritis leading to peptic ulcer and is a major risk factor for gastric malignancies. Failure in the eradication of H. pylori infection and increasing antibiotic resistance are two major problems in preventing H. pylori colonization. Hence, a deeper understanding of the bacterial survival strategies is needed to tackle the increasing burden of H. pylori infection by an appropriate intervention. Our study demonstrated that the lack of cholesteryl glucosides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
(43 reference statements)
1
25
0
Order By: Relevance
“…However, MC H pylori showed occurrence of higher amount of cholesterol (54 181 ppm) compared with NM (19 155 ppm). It has been demonstrated that accumulation of cholesterol in H pylori cell membrane increases bacterial resistance to antibiotics and reduction in cholesterol leads to susceptibility to antibiotics . Accumulation of cholesterol in H pylori cell membrane might affect bacterial cell surface properties by increasing hydrophobicity, decreasing negative charge, decreasing fluidity, and altering LPS and proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, MC H pylori showed occurrence of higher amount of cholesterol (54 181 ppm) compared with NM (19 155 ppm). It has been demonstrated that accumulation of cholesterol in H pylori cell membrane increases bacterial resistance to antibiotics and reduction in cholesterol leads to susceptibility to antibiotics . Accumulation of cholesterol in H pylori cell membrane might affect bacterial cell surface properties by increasing hydrophobicity, decreasing negative charge, decreasing fluidity, and altering LPS and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, MC H pylori showed occurrence of higher amount of cholesterol (54 181 ppm) compared with NM (19 155 ppm). It has been demonstrated that accumulation of cholesterol in H pylori cell membrane increases bacterial resistance to antibiotics 25 and reduction in cholesterol leads to susceptibility to antibiotics. 43 Furthermore, MC exhibited resistance to all the used antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori harboring CGT, inhibits interferon gamma-induced signaling, which avoids host inflammatory responses [46]. Noticeably, CGs also contribute to cell wall integrity, morphology, and antibiotic resistance [47]. Collectively, these findings highlight the multiple strategies employed by H. pylori for persistent colonization.…”
Section: Cholesterol-α-glucosyltransferase (Cgt)mentioning
confidence: 92%
“…Cholesterol and cholesteryl glucosides have no influence on the stability of the cell membrane conformation of H. pylori, and rather these steroidal compounds serve to strengthen the membrane lipid barrier of the bacteria on the limitation of the permeability of lipophilic compounds. A recent study by other group has demonstrated that cholesteryl glucosides are responsible for the morphological maintenance of H. pylori, for the acquirement of resistance to antibiotics such as polymyxin B, colistin, and tetracycline, and for the promotion of biofilm formation [47]. This suggests that cholesteryl glucosides of H. pylori play an important role to limit the membrane permeability of various low-molecular-weight compounds.…”
Section: Bactericidal Mechanism Of the Indene Compound Speciesmentioning
confidence: 99%